Religious Values Implementation Strategy On Work Culture Ministry Of Religion Office, Muara Enim District - Asmahayati Asmahayati; Linyansyah Linyansyah; Nisma Aprini (Penerbit Jurnal Indonesia, 2023)
This study aims to identify and analyze the application of religious values and work culture as well as strategies for implementing religious values in the work culture of the Office of the Ministry of Religion, Muara Enim Regency. Types of qualitative research. Analytical descriptive, data collection through documentation, observation and interviews with 10 key informants, namely civil servants who understand and master what will be studied, are easy to find and are willing to share information. Data analysis techniques use the stages of condensing data, presenting data, making and verifying conclusions. To obtain in-depth information and get a complete picture of religious values in the work culture of the Office of the Ministry of Religion of Muara Enim Regency, 8W+ 1H+1I analysis was also used; Input-Process-Output-Outcome-Benefit and SWOT Analysis The research results obtained 1. The implementation of religious values at the Office of the Ministry of Religion of Muara Enim Regency has not been implemented optimally from the aspects of work discipline, cooperation, the principle of division of tasks and ukhuwah Islamiyah. 2. The implementation of work culture at the Office of the Ministry of Religion of Muara Enim Regency has not been carried out optimally from the aspects of integrity, professionalism, responsibility and exemplary. 3. The strategy for implementing religious values in the work culture of the Office of the Ministry of Religion of Muara Enim Regency is using the SO strategy in which researchers combine various strengths with opportunities owned by the Office of the Ministry of Religion of Muara Enim Regency